Jewish Curse Tablets? - Saʿar, Orṭal-Paz (Religion in the Roman empire, 2021)
Relatively few curse tablets have been uncovered in the area covering late-antique Syria-Palaestina. Among these (with one recent exception from Antioch), none display signs of having been inscribed by Jews: they do not employ the languages associated with Judaism - Hebrew or Aramaic - nor have any of them been uncovered in locations specifically associated with Judaism, for instance in a Jewish tomb. Even though recipes found in Jewish magic manuals indicate that Jews were aware of the use of metal tablets for erotic and aggressive magical ends, the finds from Syria-Palaestina (and, incidentally, elsewhere), suggest they were not among the producers of such artefacts. Nonetheless, the notion of cursing was not alien to Judaism (intriguing resemblances exist between imprecations in the Hebrew Bible and Greco-Roman 'prayers for justice'), and cursing actions may be encountered in a variety of sources. One wonders, then, whether the typical defixiones found different modes of expression in the context of late-antique Judaism. My article asks whether there are any Jewish counterparts to typical curse tablets, and if so, how they differ from the latter: in form or also in essence? Additionally, can one identify reasons for the absence of Jewish curse tablets and for the preference for other magical means?